Upregulating Hif‐1α by Hydrogel Nanofibrous Scaffolds for Rapidly Recruiting Angiogenesis Relative Cells in Diabetic Wound. Issue 8 (18th February 2016) - Chen, Hao; Jia, Peng; Kang, Hui; Zhang, Hongbo; Liu, Yi; Yang, Peilang; Yan, Yufei; Zuo, Guilai; Guo, Lei; Jiang, Min; Qi, Jin; Liu, Yuanyuan; et al.
Abstract : Nonhealing chronic wounds on foot are one of the most dreaded complications of diabetes, and biomedical scaffolds remain an attractive option for repairing or regenerating tissues. Accelerating angiogenesis in the early stage after injury is critical to wound healing process; however, the scaffolds accelerate the angiogenesis in the beginning but with the acceleration of vessel network formation the scaffold network hinders the process. In this study, the water soluble drugs‐loaded hydrogel nanofibrous scaffolds are designed for rapidly recruiting angiogenesis relative cells and promoting wound healing. The sustained release profile of desferrioxamine (DFO), which continues for about 72 h, leads to significantly increase of neovascularization. The majority of the scaffold is degraded in 14 d, leaving enough space for cell proliferation and vessel formation. The in vitro results show that the scaffolds upregulate the expression of Hif‐1α and vascular endothelial growth factor, and enhance the interaction between fibroblasts and endothelial cells. The in vivo studies show a higher expression of angiogenesis related cytokines. This study demonstrates that the DFO released from hydrogel nanofibrous scaffolds of quick degradation can interfere with the required prolyl‐hydroxylases cofactors by acting as Fe 2+ chelator and upregulate the expression of Hif‐1α, leading to a significant increase of the neovascularization. Abstract : This study demonstrates that the desferrioxamine released from hydrogel nanofibrous scaffolds can interfere with the required prolyl‐hydroxylases cofactors by acting as Fe 2+ chelator and upregulate the expression of Hif‐1α, leading to significant increase of the neovascularization.